PENGELOLAAN PEMBELAJARAN BERBASIS PENDEKATAN BEYOND CENTERS AND CIRCLE TIME (BCCT) PADA ANAK PLAYGROUP DI SEKOLAH ALAM BOSOWA - Nurrahmatillah Nurrahmatillah; Arifuddin Siraj; A. Nur Maulana (Universitas Islam Negeri Alauddin Makassar, 2019)
This research aims to know learning management in the early childhood Bosowa Alam school with the BCCT approach. The previous main problem to be listed into a number of subproblems, namely 1) What kind of learning resources used in early childhood in the Bosowa Alam school? 2) How to manage learning toward early childhood education at Bosowa Nature School by applying BCCT and DAP? This research classified as qualitative with employing pedagogical and psychological approach. The data was taken from head master, class Guardian, Teachers and students. The data collection methods used observation, interviews, documentation, and some referencea. Techniques of data analysis carried out in three stages, namely data reduction, data presentation and conclusion collection. The results of this study indicate the fact that several things must be highly considered by educators before formulating a learning plan that will be used in early childhood of bosowa natural school. The implementation of learning supported by learning resources used in each center to be developed with 5 child domains (affection, language, cognition, social and psychomotor) and 7 multiple intelligences (logical-mathematical intelligence, Sapatial intelligence, musical intelligence, kinesthetic intelligence, Interpersonal and Intrapersonal intelligence). The management of Bosowa Alam school learning resources carried out in 5 stages: students identification, planning learning resources, preparing learning resources, using learning resources as well and evaluation methods.